Legal Framework and Criminal Sanctions for Bitcoin-Based Narcotics Transactions - Maria Dona Kristina Wati; Ainul Azizah; Fanny Tanuwijaya (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2025)
The rapid development of digital technology has transformed the global financial landscape with the emergence of virtual currencies such as Bitcoin. As a decentralized digital asset based on blockchain technology, Bitcoin enables fast, anonymous, and cross-border transactions without central authority intervention. While these features offer convenience, they also pose risks of abuse in illegal activities, including narcotics transactions. In Indonesia, the use of Bitcoin in drug-related offenses presents complex legal challenges due to the absence of explicit criminal regulations governing such usage. This study examines the criminal liability of narcotics offenders who utilize Bitcoin, focusing on three core issues: the juridical basis for punishment, the characteristics of punishment under Indonesia’s legal system, and an ideal penal concept for the future. The research employs a normative juridical method with statutory, conceptual, and case study approaches. Findings indicate that punishment remains based on Law No. 35 of 2009 on Narcotics, with Bitcoin regarded as a means rather than a core element of the crime. Although it does not constitute a new offense, its use may aggravate punishment through individualized sentencing. Sanctions involving digital assets remain suboptimal due to regulatory gaps. Therefore, this study recommends revising criminal laws to explicitly regulate Bitcoin use in drug crimes, developing sentencing guidelines that consider technological factors, and formulating responsive penal policies, including asset seizure and inter-agency collaboration through blockchain forensic technology.